Legal Certainty in Police Ethics Examinations by West Java BIDROPAM - sakur sakur; Haidan Angga Kusumah (Law and Justice research journal, 2026)
Enforcement of the Police Professional Code of Ethics is a measure of institutional accountability after the issuance of Police Regulation Number 7 of 2022. In West Java, rising ethics cases and sanctions reveal a need to assess gaps among normative procedures, examination practice, transparency, timeliness, and parties' rights.This article analyzes the conformity of KEPP examinations by West Java Bidpropam and formulates obstacles and optimization strategies under Regulation 7/2022. The study applies an empirical juridical approach with descriptive-analytical specification. Data were obtained from Police Regulation Number 7 of 2022, the Police Law, scholarly literature, KEPP case data, and field findings compiled in the thesis. The analysis is qualitative, using Hans Kelsen's legal certainty theory and Soerjono Soekanto's law enforcement theory to compare norms, practice, obstacles, and reform recommendations. Validity was strengthened through source, document, observation, and legal triangulation. The study finds that KEPP examinations follow normative stages: complaint receipt, preliminary examination, case filing, KKEP hearing, and appeal. Nevertheless, legal certainty remains suboptimal because consistency, compliance with the 30-day period, information transparency, and the rights of examined officers and complainants are not yet fully substantive. The main obstacles concern legal rules, examiners, facilities, public trust, and organizational culture. Their interaction makes delays and bias difficult to solve separately. These findings require KEPP examination reform beyond administrative compliance. The Police should strengthen SOPs, procedural sanctions, case digitalization, examiner competence, complainant protection, and internal-external oversight to restore public trust and ensure transparent, objective, accountable, and fair examinations for affected and involved parties. The article's originality lies in an empirical juridical analysis combining legal certainty and law enforcement theories to assess not only procedural existence but also implementation quality. Its focus on West Java Bidpropam offers locus-based evidence and recommendations for implementing Police Regulation Number 7 of 2022 in ethics reform.